Ḥanbalī theology - Hoover, Jon (Oxford University Press, 2016)
The modern study of Ḥanbalī theology was initially plagued by the problem of viewing Ḥanbalism through the eyes of its Ashʿarī opponents. I. Goldziher (d. 1921) and D. B. Macdonald (d. 1943) labelled the Ḥanbalīs ‘reactionary’ and bemoaned the harm that they had done to the cause of a conciliatory Ashʿarī orthodoxy. The work of H. Laoust (d. 1983) and G. Makdisi (d. 2002) turned the tide of scholarship toward closer examination of Ḥanbalī texts on their own terms and deeper understanding of Ḥanbalism in its historical context. Makdisi in particular argued that Ḥanbalism had a disproportionate impact on the development of Islamic theology because it was the only Sunnī law school to maintain a consistently traditionalist theological voice. For Makdisi, the Ḥanbalīs were the ‘spearhead’ of a wider traditionalist movement in medieval Islam against the rationalism of Muʿtazilī and Ashʿarī Kalām (Makdisi 1962–3; 1981). Aspects of Makdisi’s narrative require modification, especially as some leading Ḥanbalīs of the fifth/eleventh and sixth/twelfth centuries were more rationalist than earlier thought, but the main thrust of his argument still stands. It may be added that Ḥanbalī theology has also had a disproportionate impact on modern Islamic theology. The Wahhābī movement in Arabia and contemporary Salafism have appropriated and spread the theology of the eighth/fourteenth-century scholar Ibn Taymiyya far beyond the confines of the modern Ḥanbalī school of law. This chapter begins with the formation and early development of Ḥanbalism in order to clarify Makdisi’s claim, and it continues by surveying key Ḥanbalī figures from Aḥmad b. Ḥanbal in the third/ninth century to Ibn ʿAbd al-Wahhāb in the twelfth/eighteenth and giving extended attention to the unique theology of Ibn Taymiyya.